Preparation and Characterization of Biobased Lignin-Co-Polyester/Amide Thermoplastics - Eric L. Young (Molecules, 2021)
More than 23 million tonnes of lignin are produced annually in the US from wood pulping and 98% of this lignin is burnt. Therefore, creating products from lignin, such as plastics, offers an approach for obtaining sustainable materials in a circular economy. Lignin-based copolymers were synthesized using a single pot, solvent free, melt condensation reaction. The synthesis occurred in two stages. In the first stage, a biobased prepolymer consisting of butanediol (BD, 0.8–1 molar content) and a diacid (succinic (SA), adipic (AA) and suberic acids (SuA), with varying amounts of diaminobutane (DAB, 0–0.2 molar content) was heated under vacuum and monitored by Fourier transform infra-red (FTIR) spectroscopy and electrospray ionization-mass spectrometry (ESI-MS). In the second stage, prepolymer was mixed with a softwood kraft lignin (0–50 wt.%) and further reacted under vacuum at elevated temperature. Progression of the polymerization reaction was monitored using FTIR spectroscopy. The lignin-copolyester/amide properties were characterized using tensile testing, X-ray diffraction (XRD), dynamic mechanical analysis (DMA), differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) techniques. Lignin co-polymer tensile (strength 0.1–2.1 MPa and modulus 2 to 338 MPa) properties were found to be influenced by the diacid chain length, lignin, and DAB contents. The lignin-copolymers were shown to be semi-crystalline polymer and have thermoplastic behavior. The SA based copolyesters/amides were relatively stiff and brittle materials while the AA based copolyesters/amides were flexible and the SuA based copolyesters/amides fell in-between. Additionally, > 30 wt.% lignin the lignin- copolyesters/amides did not exhibit melt behavior. Lignin-co-polyester/amides can be generated using green synthesis methods from biobased building blocks. The lignin- copolyesters/amides properties could be tuned based on the lignin content, DAB content and diacid chain length. This approach shows that undervalued lignin can be used in as a macromonomer in producing thermoplastic materials.